The Use of Ramie By-Product (Boehmeria nivea) Materials as Complete Feed on the Growth and Hematology of Weaning Ettawa Cross Breed Goat - Susanti, Emmy (2015)
This study aims to determine the effect of complete feed using ramie with or without ensilage and vegetable or animal sources of protein towards the growth and blood hematology of weaning Ettawa cross breed goat. The study used a 2X2 factorial design and 6 (six) replicates. The complete feed treatment using ramie by-product without ensilage showed that almost all parameters of growth was higher than the ensilaged one (P<0.05) except height. Complete feed treatment using ramie by-product with an additional source of animal protein indicates the final weight and daily weight gain (PBBH) was higher (P<0.01). The interaction of both treatments was proved the final weight, daily weight gain, and chest circumference. The complete feed treatment using ramie without and with ensilage, the addition of a source of protein and the interaction of both treatments had no effect on the blood hematology. The study could be concluded the weaning Ettawa cross breed goat that received complete feed using ramie waste without ensilage showed higher growth while the addition of animal protein sources are higher